Factors associated with dental cavity in children aged six to 36 months old, in Salvador-BA - Maria Lizzia Moura Ferreira dos Santos; Maria Cristina Teixeira Cangussu; David José Casimiro de Andrade (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to analyze the factors associatedwith dental cavity in early childhood. Methods: this is a cross-sectional study on oral health condition of 535 children aged between six and 36 months old, at Family Health Units, in Salvador-BA. Information was collected on socioeconomic conditions, mother and child's health, eating and oral hygiene habits, and oral examination. Results: the prevalence of dental cavity was 13.64% (CI95%=11.44 -15.84) and the factors associated were: child's age, number of rooms in the house, "Bolsa Família" (Family Welfare) benefit, prenatal consultations, birth weight and exclusive breastfeeding. Conclusions: socioeconomic conditions strongly influenced oral health, as well as prenatal care and breastfeeding. To prevent childhood cavities, it is pertinent to invest in intersectoral actions and systematized programs, including the medical and nursing staff, as these actions are essential for integral care for the child's health and quality of life